2022
DOI: 10.1101/2022.11.04.515184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seeing our hand or a tool during visually-guided actions: different effects on the somatosensory and visual cortices

Abstract: The processing of proprioceptive information in the context of a conflict between visual and somatosensory feedbacks deteriorates motor performance. Previous studies have shown that seeing one's hand increases the weighting assigned to arm somatosensory inputs. In this light, we hypothesized that the sensory conflict, when tracing the contour of a shape with mirror-reversed vision, will be greater for participants who trace with a stylus seen in their hand (Hand group, n=17) than for participants who trace wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 66 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…It has been suggested that the dynamic suppression of cortical somatosensory inputs observed in individuals performing goal-directed movements under conflicting visuosomatosensory feedback serves to partially resolve the sensory conflict 20,47,48 . This sensory gating was observed in the Tactile group, but not in the NoTactile group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the dynamic suppression of cortical somatosensory inputs observed in individuals performing goal-directed movements under conflicting visuosomatosensory feedback serves to partially resolve the sensory conflict 20,47,48 . This sensory gating was observed in the Tactile group, but not in the NoTactile group.…”
Section: Discussionmentioning
confidence: 99%
“…Proprioception plays a crucial role in motor control by providing the brain with information about the position, orientation, and movement of various body parts, including the fingers 49 . Previous studies exploiting the mirror paradigm reported gating over the somatosensory cortex even when participants traced a shape with the tip of a pen 20,48 . In this light, one might question why the tracing performance and the activity of the source-localised somatosensory cortex were unaffected by the mirror-reversed visual in the NoTactile group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation